2017
DOI: 10.1186/s13063-017-2158-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intensive nutrition intervention of a high protein and low glycemic-index diet on weight of kidney transplant recipients: study protocol for a randomized clinical trial

Abstract: BackgroundExcessive weight gain is commonly observed within the first year after kidney transplantation and is associated with negative outcomes, such as graft loss and cardiovascular events. The purpose of this study is to evaluate the effect of a high protein and low glycemic-index diet on preventing weight gain after kidney transplantation.MethodsWe designed a prospective, single-center, open-label, randomized controlled study to compare the efficacy of a high protein (1.3–1.4 g/kg/day) and low-glycemic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…The Kidney Disease Improving Global Outcomes (KDIGO) guideline for CKD patients recommends to avoid excessive protein intake (>1.3 g/kg/d) in non-diabetic CKD-patients with an eGFR > 30 mL/min/1.73 m 2 [50]. Currently, no specific recommendations are available for KTR, but an ongoing dietary intervention study in 120 KTR, aiming to evaluate the effect of a high-protein (1.3-1.4 g/kg/d) low-glycemic-index diet on prevention of post-transplant weight gain, may provide more insight in the optimal protein intake after kidney transplantation [51]. With the high prevalence of overweight, obesity and its cardio-metabolic derangement, as well as the high risk of malnutrition, tailored dietary advice in collaboration with a renal dietician is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kidney Disease Improving Global Outcomes (KDIGO) guideline for CKD patients recommends to avoid excessive protein intake (>1.3 g/kg/d) in non-diabetic CKD-patients with an eGFR > 30 mL/min/1.73 m 2 [50]. Currently, no specific recommendations are available for KTR, but an ongoing dietary intervention study in 120 KTR, aiming to evaluate the effect of a high-protein (1.3-1.4 g/kg/d) low-glycemic-index diet on prevention of post-transplant weight gain, may provide more insight in the optimal protein intake after kidney transplantation [51]. With the high prevalence of overweight, obesity and its cardio-metabolic derangement, as well as the high risk of malnutrition, tailored dietary advice in collaboration with a renal dietician is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…We included 730 KTR with a study visit at a median of 4.1 [IQR 1.0-11.0] years after transplantation. Subjects were 58 [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] years of age, 57% were male, and mean eGFR was 51.2 ± 17.9 mL/min/1.73 m 2 . A combined organ transplantation was performed in 20 KTR, of which 17 received a combined kidney-pancreas transplantation and 3 received a combined kidney-liver transplantation.…”
Section: Baseline Characteristics Of Total Population and Across Catementioning
confidence: 99%
“…Patients with KTx in the present clinical trial will undergo an individualized nutritional intervention for 12 months after surgery. This period of nutritional intervention was selected based on previous studies, which demonstrated that protein intake is associated with maintenance of kidney function in the first year post-KTx [30][31][32]. However, studies on the assessment of the impact of dietary protein intake in post-KTx patients remain scarce and controversial [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In a very small study that assessed the effect of an intensive lifestyle intervention comprising physical exercise, behavioural interventions and nutritional guidance in obese KTRs, after 12 months the intervention group was weight-stable and had improvements in body composition (greater lean mass), whereas the BMI of patients in the control group increased on average from 38 to 46 kg/m 2 [144]. Trials assessing the effect of lifestyle interventions on the prevention of weight gain after KT are currently ongoing [102,145].…”
Section: Obesitymentioning
confidence: 99%